The Digital Transformation of Morocco’s Public Administration: Progress, Challenges, and Prospects - ElBachiri, Souhaila; Lehim, Hind; ElHammioui, Linda; Daoui , Driss (Revue Internationale des Sciences de Gestion, 2025)
Since the early 2000s, the digitization of public services has become a key priority for governments worldwide, aiming to enhance administrative efficiency, transparency, and citizen engagement. Morocco has followed this global trend, initiating its digital transition with early efforts such as the creation of the Agence Nationale de Réglementation des Télécommunications (ANRT) in 1997 and the adoption of a national ICT development policy in 2002. This momentum intensified with the launch of the national digital transformation plan in 2016, which seeks to modernize public administration and stimulate economic growth through the dematerialization of services. Today, Morocco has made significant progress, offering a wide range of online services, from electronic signatures to digital portals for administrative procedures. This digital shift raises important questions about the impact of technology on administrative performance: Can digitization improve the quality and accessibility of public services, reduce bureaucratic delays, and enhance the transparency and accountability of public decisions? This paper explores how the digital transformation of Morocco’s public administration contributes to a new model of administrative efficiency in the digital age.